Ichabod Chase Co. (New Bedford, Mass.) records - Ichabod Chase Co. (New Bedford, Mass.)
Accounting journal (1857 January-1858 February) including transactions for the purchase of raw materials, subcontracting, manufacturing, and labor. Customers include individuals and vessels engaged in whaling.
Coopering firm.
Collection material in English.
Keywords: Coopers and cooperage -- Massachusetts -- New Bedford; Whaling -- Massachusetts -- New Bedford